Fi Ra Wali: Revitalisasi Folklor “Saguku Hidupku” Sebagai Identitas Kultural dalam Kosmologi Masyarakat Sentani-Papua - Cleopatriza Thonia Ruhulessin (Jurnal Filsafat "WISDOM", 2020)
This article aims to describe and explain how the philosophy of fi ra wali (in English: my sago my life) shapes the identity of Sentani people. The objective is to explain this notion (fi ra wali) features as the cultural identity of the Sentani people whichconstructed in everyday engagement (daily interactions) of the Sentani communities. Data for the study was obtained through  ethnographic research and phenomenology techniques including participant observation, interviews and literature study. Identity is usually constructed institutionally based on juridical and normative agreements collectively. This article reveals that identity can be constructed narratively, in daily interactions in society. Everyday angagement (daily life) gives birth to authentic experiences that are sacred in social relations, both in physical space and spiritual space of the Sentani people. Identity shapedfrom cosmic-cultural reality that exists in cosmology, is able to integrate society in sui generis (clans), in order to face modernization, which has caused social changes in Sentani society. This article concludes that the fi ra wali as a cultural identity has important contribution to deal with multicultural contexts.